The influence of orthodontist change on treatment duration and outcomes in patients treated with Clark’s twin block appliance followed by non-extraction fixed mechanotherapy – a retrospective cohort study - Rizwan Khalil; Rashna Hoshang Sukhia; Mubassar Fida (BMC Oral Health)
Abstract Background Post-graduate resident turnover in public and teaching hospital orthodontic clinics often leads to challenges in maintaining the same level of efficacy when a care provider changes during orthodontic treatment. This retrospective cohort study aimed to compare the duration and quality of treatment outcomes between two patient groups: the transfer group, who underwent orthodontic care from multiple residents, and the non-transfer group, whose entire treatment was overseen by a single resident. Methods Sixty-six patients were enrolled and equally divided into transfer and non-transfer groups. Orthodontic treatment in both groups was completed with Clark’s twin block appliance followed by non-extraction fixed mechanotherapy. Their pre- and post-treatment dental casts and panoramic radiographs were used to evaluate the quality of treatment outcomes utilizing the American Board of Orthodontics Cast-Radiograph Evaluation (ABO-CRE) and Peer Assessment Rating (PAR) indices. Mann-Whitney U test was used to assess the treatment time and quality between the two groups. Results There was an insignificant difference in the post-treatment outcomes between the two groups as evaluated by ABO-CRE (p = 0.691) and PAR (p = 0.926). The Shapiro-Wilk test revealed a non-normal distribution of the variables. In both the transfer and control groups, the mean and standard deviation of the duration of treatment were 56.12 ± 19.68 months and 35.09 ± 6.94 months, respectively. Conclusions Transferred patients had more visits and longer treatment duration, yet treatment quality remained comparable to the control group despite the extended duration in transfers.